2011
DOI: 10.1590/s2175-78602011000400012
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophytic Cyperaceae from the Araguaia river basin, Brazil

Abstract: Cyperaceae is a cosmopolitan family with over 5,000 species, which are often found in wet habitats. In this study we found 31 hydrophylic species of Cyperaceae, belonging to 10 genera (Ascolepis, Calyptrocarya, Cyperus, Eleocharis, Fimbristylis, Fuirena, Lipocarpha, Pycreus, Rhynchospora and Scleria), that occur in the Araguaia River Basin, located mainly within the Brazilian Cerrado (savanna). Short descriptions, geographic distribution, illustrations, identification keys and comments are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…The significant presence of the Cyperaceae family recorded in this study was also identified in Central Amazon (Junk and Piedade, 1993), in the Araguaia River basin (Oliveira et al, 2011), andin northeastern Brazil (Moura-Júnior et al, 2013).…”
Section: Ruedasupporting
confidence: 78%
“…The significant presence of the Cyperaceae family recorded in this study was also identified in Central Amazon (Junk and Piedade, 1993), in the Araguaia River basin (Oliveira et al, 2011), andin northeastern Brazil (Moura-Júnior et al, 2013).…”
Section: Ruedasupporting
confidence: 78%
“…Thus, the real diversity of the aquatic flora from the Brazilian Cerrado will be better known through studies carried out by specialists focusing on aquatic habitats on the region. Our efforts to improve the knowledge of the aquatic flora from the Araguaia River basin have resulted in the discovery of new species (Koehler and Bove 2001, Oliveira et al 2011) and on the better understanding of taxonomic groups such as the Alismatales (Koehler and Bove 2004) and Cyperaceae (Gil et al 2007, Oliveira et al 2011). As a result of an intensive search of collections and field work, we provide here an annotated list of aquatic and marshy monocots found in the Araguaia River basin.…”
Section: Introductionmentioning
confidence: 99%
“…Ilustração das espécies estão referidas às obras consultadas para a identificação das mesmas: Barros (1960), Guaglianone (1980), Araújo & Longhi-Wagner (1996); Trevisan et al (2007);Ferreira & Eggers (2008); Silveira & LonghiWagner (2008); ; ; Oliveira et al (2011);Hefler & Longhi-Wagner (2012); Silveira & LonghiWagner (2012).…”
Section: Methodsunclassified